Molecular characterization and expression analysis of toll-like receptor 2 in response to bacteria in silvery pomfret intestinal epithelial cells. (November 2016) - Gao, Quanxin; Xiao, Yingping; Zhang, Chenjie; Min, Minghua; Peng, Shiming; Shi, Zhaohong
Abstract: Toll-like receptor 2 (TLR2) has been shown to play a crucial role in the host defense of pathogenic microbes in innate immunity. In this study, the full-length cDNA of TLR2 in silvery pomfret ( Pampus argenteus ) was cloned by homology cloning and the rapid amplification of cDNA ends (RACE) technique. The complete cDNA sequence of TLR2 was 2932 bp, containing an open reading frame (ORF) of 2469 bp encoding 822 amino acids. A multiple alignment analysis of the silvery pomfret TLR2 protein-coding sequence with other known TLR2 sequences from Oplegnathus fasciatus, Epinephelus coioides, Larimichthys crocea, Miichthys miiuy, Oreochromis niloticus, Paralichthys olivaceus, Trematomus bernacchii, Sparus aurata, and Chionodraco hamatus exhibited a high degree of homology of 78.83%, 75.91%, 74.21%, 74.94%, 71.95%, 72.57%, 73.68%, 75%, and 72.52 respectively, between these fish. Analysis of the TLR2 domain structures indicated that TLR2 from the silvery pomfret has the typical structural features of proteins that belong to the TLR family, including one transmembrane domain, eleven leucine-rich repeats (LRRs), and one Toll/IL-1 receptor homology domain (TIR). In vitro immunostimulation experiments revealed that Lactobacillus plantarum and Clostridium butyricum induce high levels of TLR2 mRNA and protein expression, but they induce only moderate levels of IL-8 and TNF-α production compared to Vibrio anguillarum . This suggests that TLR2 might play a vital role in the L. plantarum and C. butyricum -mediated immune response. In contrast, V. anguillarum significantly increased the secretion of IL-8 and TNF-α and induced cell apoptosis and necrosis. Due to the lower expression of TLR2 and higher levels of IL-8 and TNF-α induced by V. anguillarum, we hypothesize that a V. anguillarum infection is independent of the TLR2-induced production of pro-inflammatory cytokines. These results indicate that TLR2 may be involved in molecular interactions between the host and commensal bacteria, that exist in the silvery pomfret intestinal tract. Highlights: The complete cDNA sequence of silvery pomfret TLR2 is 2932 bp, containing an open reading frame (ORF) of 2469 bp. Silvery pomfret TLR2 has a high sequence homology with Oplegnathus fasciatus, Epinephelus coioide and Larimichthys crocea . TLR2 from the silvery pomfret has the typical structural features of proteins that belong to the TLR family, including one transmembrane domain, eleven LRRs, and oneTIR. TLR2 might play a vital role in the L. plantarum and C. butyricum -mediated immune response.